Spatial Heterogeneity of Long-Term Sandy Shoreline Change Along Eastern Hainan Island, China (1987–2025) - Yuanting Ding; Yi Liu; Qiyi Du; Jitao Yu (Journal of Marine Science and Engineering, 2026)
Long-term shoreline change on tropical islands is spatially heterogeneous, but alongshore contrasts remain insufficiently resolved. We quantified shoreline change along the 151.1 km eastern sandy coast of Hainan Island, China, from 1987 to 2025 using Landsat-derived visually interpreted shoreline proxies and the Digital Shoreline Analysis System across 1413 transects. The coast was broadly stable to accretional, with a mean linear regression rate (LRR) of 0.49 m/yr and a mean net shoreline movement (NSM) of 17.72 m. Under the uncertainty-aware classification, 28.0% of transects were stable, 42.1% accretional, 8.2% erosional, and 21.7% indeterminate. For descriptive comparison, the eight sectors were grouped into three broad alongshore zones: a stable northern zone (Beaches A–B), an accretion-dominated central zone (Beaches C–E), and a heterogeneous southern zone (Beaches F–H). The strongest accretion occurred at Beach D (LRR = 7.63 m/yr), whereas the strongest erosion occurred south of the offshore artificial island at Beach F (LRR = −3.97 m/yr). These contrasts show that coast-wide stability or accretion can mask localized erosion. The observed patterns were spatially associated with differences in headland-bay morphology, nearshore seagrass beds, engineering structures, estuarine processes, and lagoon-inlet settings. The findings support beach-sector monitoring and differentiated coastal management.

In vivo CAR-T: a paradigm shift in adoptive cell therapy from bench to beside - Yuanting Cai; Huilei Miao; Yuning Wang; Jiatong Ding; Peiwen Ma; Xiaosong Zhong; Yue Bai; Hengjia Tu; Zhongwei Xu; Guo Zhao; Zhangqiang Xiang; Shuhang Wang; et al. (Science Bulletin, 2026)

Comparative analysis of nutritional and flavor compound alterations in Cordyceps militaris juice fermented by single or mixed Lactobacillus strains - Zeyang Li; Zhongxu Sun; Qingping Wu; Huiying Huang; Yuanting Tang; Jingwei Nan; Zhenjun Zhu; Yu Ding (Food Research International, 2025)

Expediting the integration of China into the global rare disease drug development and approval - Jiatong Ding; Huiyao Huang; Yuning Wang; Yiru Hou; Guo Zhao; Yuanting Cai; Shuhang Wang; Xuebo Zhang; Ning Li (Science Bulletin, 2025)

Baseline Plasma GPX3 Level Predicts Efficacy of Insulin-Sensitization Drug Chiglitazar in Type 2 Diabetes - Zehui Cao; Haonan Chen; Qiaochu Chen; Chen Ding; Leming Shi; Yuanting Zheng (Phenomics, 2025)

Roles of extracellular vesicles on macrophages in inflammatory bone diseases - Yifan Lin; Ziyan Wang; Shirong Liu; Jiaohong Liu; Zhiyi Zhang; Yuanting Ouyang; Zhikang Su; Ding Chen; Lvhua Guo; Tao Luo (Molecular and Cellular Biochemistry, 2024)

Effects of shore-normal coastal structure on medium- to long-term embayed shoreline evolution - Jitao Yu; Yuanting Ding; Pei Liu; Renfu Fan; Lin Zhang (Acta Oceanologica Sinica, 2024)

Erosion hotspot identified along the sandy coast of Shanwei: characteristics and origin - Jitao Yu; Yuanting Ding; Lin Zhang; Pei Liu; Renfu Fan (Acta Oceanologica Sinica, 2023)

The role of PIWI-interacting RNA in naringin pro-angiogenesis by targeting HUVECs - Yixing Pi; Zitian Liang; Qianzhou Jiang; Ding Chen; Zhikang Su; Yuanting Ouyang; Zhiyi Zhang; Jiaohong Liu; Siyi Wen; Li Yang; Tao Luo; Lvhua Guo (Chemico-Biological Interactions, 2023)

The role of Th17 cells: explanation of relationship between periodontitis and COPD? - Jiaohong Liu; Yuanting Ouyang; Zhiyi Zhang; Siyi Wen; Yixing Pi; Ding Chen; Zhikang Su; Zitian Liang; Lvhua Guo; Yan Wang (Inflammation Research, 2022)

Beach morphodynamic characteristics and classifications on the straight coastal sectors in the west Guangdong - Yuanting Ding; Jitao Yu; Huangxin Cheng (Journal of Geographical Sciences, 2020)

Wave-dominated, mesotidal headland-bay beach morphodynamic classsfications of the Shuidong Bay in South China - Jitao Yu; Yuanting Ding; Huangxin Cheng; Lailiang Cai; Zishen Chen (Acta Oceanologica Sinica, 2016)